Asymmetric Information and List Price Reductions in the Housing Market - Erik R. de Wit; Bas van der Klaauw (Tinbergen Institute, 2010)
In housing markets with asymmetric information list prices may signal unobserved properties of the house or the seller. Asymmetric information is the starting point of many models for the housing market. In this paper, we estimate the causal effect of list-price reductions to test for the presence of asymmetric information. We use very rich and extensive administrative data from the Netherlands. Our empirical results show that list-price reductions significantly increase the probability of selling a house, but also the rate of withdrawal from the market increases.
Keywords: C41; D82; R21; R31; 330; Time-on-the-market; duration analysis; transaction prices; selectivity; Immobilienpreis; Asymmetrische Information; Wohnungsmarkt; Niederlande